Do UML object diagrams affect design comprehensibility? Results from a family of four controlled experiments. (August 2017) - Torchiano, Marco; Scanniello, Giuseppe; Ricca, Filippo; Reggio, Gianna; Leotta, Maurizio
Highlights: We studied whether the use of object diagrams improves software design comprehension. We conducted a family of four controlled experiments with 124 participants in total. The benefits from object diagrams depend on both experience and familiarity with UML. The presence of object diagrams induces no additional time burden. Abstract: Objective : The main objective of our study is to assess whether the use of UML (Unified Modeling Language) object diagrams improves comprehensibility of software design when this kind of diagrams is added to UML class diagrams. Method : We have conducted a family of four controlled experiments. We involved groups of bachelor and master students. Results : Results suggest that the use of object diagrams does not always introduce significant benefits in terms of design comprehensibility. We found that benefits strongly depend on the experience of participants and their familiarity with UML. More experienced participants achieved better design comprehensibility when provided with both class and object diagrams, while less experienced seemed to be damaged when using class and object diagrams together. Results also showed the absence of substantial variations in the time needed to comprehend UML models, with or without object diagrams. Implications : Our results suggest that it is important to be aware and take into account experience and UML familiarity before using object diagrams in software modeling.